2023
DOI: 10.3390/jcm12185978
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Revascularisation versus Open Surgery with Prosthetic Bypass for Femoro-Popliteal Lesions in Patients with Peripheral Arterial Disease

Gladiol Zenunaj,
Pierfilippo Acciarri,
Giulia Baldazzi
et al.

Abstract: Aim: Complex atherosclerotic femoro-popliteal lesions have traditionally been treated with bypass surgery. A prosthetic graft is used to save the vein graft for more distal revascularisations or when a vein graft is unavailable. The endovascular approach has gained popularity and is offered as a first-line strategy for complex lesions. This study aimed to evaluate whether endovascular procedures can be used as a first-line treatment strategy for complex native femoro-popliteal lesions over open surgery with pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The approach to SFA revascularization has changed significantly with the development of more advanced and effective endovascular devices tailored to different lesions and procedural stages. There are currently many proponents of the "endovascular first" approach, stating higher patency rates and lower major adverse limb events compared to prosthetic grafts at 24 months [6]. In a large randomized BASIL-2 trial, the ''endovascular first" strategy was even shown to be superior than venous bypass for infra-popliteal revascularization in patients with CLTI [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to SFA revascularization has changed significantly with the development of more advanced and effective endovascular devices tailored to different lesions and procedural stages. There are currently many proponents of the "endovascular first" approach, stating higher patency rates and lower major adverse limb events compared to prosthetic grafts at 24 months [6]. In a large randomized BASIL-2 trial, the ''endovascular first" strategy was even shown to be superior than venous bypass for infra-popliteal revascularization in patients with CLTI [3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found largely conflicting evidence on which method is superior to revascularize total SFA occlusions. Both non-randomized and randomized trials have indicated the superiority of open surgery over endovascular treatment [4,5], and vice versa [3,6,7], especially if the autologous saphenous vein is not available for bypass. Due to its less invasive nature, endovascular treatment generally provides a lower morbidity, periprocedural mortality, and length of hospital stay [6,7], whereas open surgery provides lower rates of major adverse limb events and death in the long term [4].…”
Section: Introductionmentioning
confidence: 99%
“…In CLTI, the results of bypass surgery using an autologous vein are significantly better than those of endovascular therapy. The difference disappears when synthetic prostheses are used as bypass material [51,52], or may even favour endovascular therapy in patients who no longer have a vein as a bypass vessel [53]. Prosthetic bypasses should be regarded as the last resort before major amputation, owing to the risk of infection considering the diabetic patients' immunodeficiency.…”
Section: Revascularizationmentioning
confidence: 99%